THE ENTERTAINMENT INDUSTRY AS A STRATEGIC SEGMENT OF THE DIGITAL ECONOMY - YANKOVOI, Roman; MYKOLAICHUK, Vasyl (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article delves deeply into the entertainment industry, presenting it as not only a central part of the global creative economy but also a strategically significant pillar of the modern digital economy. It explores how digital transformation is reshaping this sector, driven by rapid advancements in technologies such as big data analytics, artificial intelligence (AI), machine learning, blockchain, virtual reality (VR), and augmented reality (AR). These tools are redefining how content is produced, distributed, consumed, and monetized. The author provides a comprehensive overview of how these technologies contribute to new value chains, improve user engagement, and stimulate innovation in business models.The study focuses on the evolution of platform-based ecosystems, where seamless interaction between creators and consumers is facilitated in real time. These platforms not only serve as content hubs but also as collaborative spaces that foster co-creation and personalization of digital experiences. Particular emphasis is placed on the convergence between the entertainment sector and digital tourism, highlighting emerging trends such as gamification of cultural heritage, immersive VR experiences for travelers, interactive storytelling, and the rise of cyber-tourism through multimedia platforms. This cross-sectoral integration enhances both user experience and economic potential.The article also addresses global patterns of digital entertainment development while shedding light on specific national-level challenges, especially those faced by Ukraine. These include the fragmentation of domestic digital markets, limited venture capital accessibility, and insufficient institutional frameworks for innovation support. Through qualitative analysis and policy evaluation, the author justifies the urgent need for a cohesive national strategy aimed at nurturing the digital entertainment sector. Such a strategy should emphasize innovation incentives, support for local content producers, development of sustainable digital infrastructures, public-private partnerships, and alignment with European digital integration goals.The findings and insights from this research can be utilized by policymakers, media professionals, cultural strategists, regional development agencies, and digital marketers. They provide a robust foundation for crafting forward-looking cultural policies, enhancing competitive digital services, and enabling sustainable development in the context of a rapidly evolving digital landscape.
Keywords: entertainment industry; digital economy; digital transformation; business model; platform; digital tourism; media ecosystem; innovation; creative economy; VR/AR technologies; digital policy